2013
DOI: 10.3846/16111699.2012.670134
|View full text |Cite
|
Sign up to set email alerts
|

Inflation, Inflation Uncertainty and Growth in the Iranian Economy: An Application of Bgarch-M Model With Bekk Approach

Abstract: This paper investigates the relationship between inflation, economic growth and their respective uncertainties in Iran for the period of 1988–2008 by using quarterly data. We employ a Bivariate Generalized Autoregressive Conditional Heteroskedasticity-in-Mean (BGARCH-M) model to examine in a unified empirical framework all the possible interactions between inflation uncertainty and growth in Iran. The model is simultaneously estimated by using the maximum log-likelihood method with the BEKK approach. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…He observed that inflationary periods yield high inflation uncertainty. His evidence supported the Friedman–Ball hypothesis, as seen in the study of Heidari and Bashiri (2010) in Iran, and Nasr et al (2015) in South Africa. In contrast, Chowdhury (2014) obtained a two-way causal link between the two variables, confirming both the Friedman–Ball and Cukierman–Meltzer hypotheses.…”
Section: Single Country Evidencesupporting
confidence: 63%
“…He observed that inflationary periods yield high inflation uncertainty. His evidence supported the Friedman–Ball hypothesis, as seen in the study of Heidari and Bashiri (2010) in Iran, and Nasr et al (2015) in South Africa. In contrast, Chowdhury (2014) obtained a two-way causal link between the two variables, confirming both the Friedman–Ball and Cukierman–Meltzer hypotheses.…”
Section: Single Country Evidencesupporting
confidence: 63%
“…One can observe from the empirical literature that a major part of the previous studies found evidence in favour of the Friedman-Ball hypothesis. Some examples of these studies show that an increase in inflation led to an increase in inflation uncertainty in the G7 countries (Grier & Perry, 1998), in certain European countries (Fountas et al, 2004;Hasanov & Omay, 2011;Lawton & Gallagher, 2020;Pintilescu et al, 2014), in the United Kingdom (Kontonikas, 2004), in Japan (Wilson, 2006), in Taiwan (Chen et al, 2006, in the Caribbean countries (Payne, 2008), in El Salvador (Payne, 2009a), in Thailand (Payne, 2009b) and in Iran (Heidari et al, 2013). In addition, certain studies yielded that an increase in inflation uncertainty resulted in an increase in inflation in the United States (Berument et al, 2009;Bhar & Mallik, 2010), as well as in certain advanced economies (Fountas, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Included in the body of literature are studies by Grier and Perry (1998), Bhar and Hamori (2004), Balcilar and Ozdemir (2013) and Chowdhury and Sarkar (2015), who considered the Group of Seven (G7); Fountas (2001), Fountas et al (2004), Kontonikas (2004) and Lawton and Gallagher (2020), who focussed on European countries; Jiranyakul and Opiela (2011), Jiang (2016), Su et al (2017) and Jiranyakul (2020), who considered Asian economies; Asghar et al (2011) and Chowdhury (2014) for South Asia; and Daal et al (2005) and Barnett et al (2020), who looked at a subset of both developed and emerging economies—which allows the authors to investigate the inflation–inflation uncertainty nexus under different hypotheses, which include conventional vs unconventional monetary policy, explicit vs implicit inflation targets, independent vs dependent central banks and calm vs crisis periods. Looking at emerging economies, Nas and Perry (2000) and Apergis et al (2021) considered Turkey; Entezarkheir (2006), Nazar et al (2010) and Heidari et al (2013) investigated Iran; and Payne (2008) examined three Caribbean countries. Papers focusing on African countries—which have not procured much deliberation in the empirical literature—are studies by Achour and Trabelsi (2011) and Sharaf (2015), who looked at Egypt; Valdovinos and Gerling (2011), who focussed on eight affiliate countries of the West African Economic and Monetary Union (WAEMU) ; Hegerty (2012), who looked at nine SSA countries ; Barimah (2014), who examined Ghana; Bamanga et al (2016), who examined Nigeria; and Alimi (2017), who studied 44 African countries.…”
Section: Literature Reviewmentioning
confidence: 99%